Manifestasi Nilai-Nilai Pendidikan Islam Dalam Lingkungan Keluarga - Rochmad, Rochmad (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
Islamic Religious Education is expected to be able to produce human beings who are always trying to perfect faith, piety, and have noble character, noble character includes ethics, character, or morals as a manifestation of Education. Within the family there is also a process of internalizing Islamic Education Values, namely the process of transferring behavior that is controlled externally to behavior that is controlled internally. Where everything can be done through the habituation process. So habituation does not only stop at school, but is also applied at home. If at school the teacher is the controller, then when at home the task is transferred to the parents. Even when the child has not yet entered school, this task has become the obligation of the parents. With the inductive method, parents place more emphasis on understanding than coercion without reason and focus children's attention on the consequences that can impact themselves, others, and the environment, so parents have been able to provide moral nutrition to help contribute to the success of character education.